PENURUNAN PERMUKAAN AIR DANAU ANEUK LAOT DI PULAU WEH PROPINSI NANGROE ACEH DARUSSALAM - Edyanto, CB Herman (Jurnal Hidrosfir Indonesia, 2008)
One of the main duties of the Local Government of Sabang was the preparation of fresh water for the people which is supplied from the lake of Aneuk Laot in WehIsland. The problem concerning with this lake is that the water level become decreasing significantly. Earthquake in a big scale which was occured in the year of 2004 was pointed at the causal factor to enlarge breaking residing in lake base. To find the answer of it, therefore, should be met.